Determining relative frequency of leukoedema and evaluation of its risk factors in patients referring to the Department of Oral Medicine in Isfahan Faculty of Dentistry - Fatemeh Basij; Farimah Sardari; Parichehr Ghalaiani (Isfahan University of Medical Sciences, 2011)
Introduction: Leukoedema is a chronic condition of the oral mucosa with an unknown etiology; its prevalence has been reported differently in different studies. The aim of this study was to determine the relative frequency of leukoedema and the associated risk factors in patients referring to the Department of Oral Medicine in Isfahan Faculty of Dentistry.Materials and Methods: In this prospective-descriptive study, the oral mucosa of 404 patients referring to the Department of Oral Medicine was examined. Data on smoking, unusual habits (cheek biting and use of hot drinks) and systemic diseases were recorded based on a checklist. Data was analyzed by chi-squared test and Fisher's test using SPSS program (α = 0.05).Results: The relative frequency of leukoedema was 23%. Mean age of the subjects was 31.56%. There was a significant relationship between the relative frequency of leukoedema and smoking, cheek chewing and habitual drinking of hot liquids (p value < 0.001). In addition, a significant relationship was observed between leukoedema frequency and anemia (p value = 0.022).Conclusion: Leukoedema was more prevalent in male, in 20-39 age group, and anemic patients. Habitual cheek chewing and hot drinks were risk factors for leukoedema. Smoking seems to have the greatest role in leukoedema, intensifying the effect of other factors. Key words: Leukoedema, Prevalence, Risk factor.